(untitled) (Texas Journal of Engineering and Technology, 2022)
This paper presents a controllable and adaptable computer virus detection model based on immune system, improves the immune mechanism of the model by introducing the thought of variable detector radius, and achieves the detector radius be set and adjusted automatically. The virus detection model has some effects on solving the conflict between the number of detectors and the scope of detection. Thus, it enables the system to have better dynamic and self-adaptability